SPEECH THERAPY METHODS FOR DEVELOPING WRITTEN SPEECH IN STUDENTS WITH HEARING IMPAIRMENTS - Toshpulova , Nodira (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyzes the speech therapy methods of developing written speech in students with hearing impairments from a scientific, theoretical and practical perspective. The study highlights the process of developing written speech based on the interrelationship of the language system, cognitive activity and speech development. It is argued that phonetic-phonological, lexical and grammatical deficiencies resulting from hearing impairments directly affect the quality of written speech. The article systematically highlights the main areas of speech therapy work, such as articulatory training, the development of phonemic perception, the enrichment of the lexical-grammatical structure and the methods of developing coherent written speech. It also substantiates the effectiveness of visual supports, a multimodal approach, step-by-step training and individual-differential methods.